Models and Estimation of Genetic Effects - Rong-Cai Yang (Frontiers Research Topics, 2015)
Ronald Fisher needed to develop elaborate models of genetic effects in order to set the foundations of Quantitative Genetics in his 1918 paper "The correlation between relatives on the supposition of Mendelian inheritance". Since then, many significant implementations have been made to model genetic effects. However, at the verge of one century after Fisher's kick-off, models of genetic effects keep on being discussed and implemented. Indeed, the relatively recent advent of QTL analyses challenged the state of the art of this field by providing researchers the opportunity to obtain and analyze estimates of genetic effects from real data. In this context, the development of this field was not exempt of some polemics, like the debate about the convenience of the functional and the statistical epistasis approaches. This research topic is meant to provide recent developments in models and estimation of genetic effects and to enrich the discussion about how and why models of genetic effects must be further developed and applied. The articles in this Research Topic shall thus extend, refine and/or provide a refresh look at Fisher's original models of genetic effects and their application to genetic effects estimation and to improve our understanding of evolutionary processes and breeding programs.